Two-dimensional covalent-organic frameworks for ultrahigh iodine capture - Li, Jinheng (2022)
Radioactive iodine in nuclear waste is increasingly harmful to nature with continuous development and utilization of nuclear energy. Herein, two new two-dimensional covalent-organic frameworks (COFs, TJNU-201 and TJNU-202) were designed and synthesized by using sterically hindered 1,3,5-trimethyl-2,4,6-tris(4-aminophenyl)-benzene as a three-connected building block. Both COFs showed ultrahigh iodine capture capacity (5.625 g/g for TJNU-201 and 4.820 g/g for TJNU-202), which can be attributed to the physical-chemical adsorption.